Pengembangan Kewirausahaan Mahasiswa Melalui Produksi Kopi- Pro - Feliatra, Feli; Batubara, Ummi Mardhiah; Nursyirwani, Nursyirwani; Umar, Lazuardi; Zevira, Bella Permata; Gustina, Julia; Alfarisy, M. Phyto; Feliatra, Pamela Isya (Civiliza Publishing, 2024)
Pro coffee is a coffee drink enriched with B.cereus consortium bacteria. Bacillus cereus is a single cell protein that is rich in protein. This program aims to develop student entrepreneurial activities by implementing the results of previous research, namely utilizing probiotic bacteria for healthy coffee entrepreneurship by adding probiotic bacteria to coffee drinks. The method used to provide lectures and practices about professional coffee processing to students involved in this service. This service activity is carried out in four stages, namely: Training and Competency Improvement. Training and competency improvement activities are carried out as an effort to increase the knowledge and competence of Partners and students in processing Pro coffee. The results of the service show that students are able to improve: 1) Knowledge of making media for developing probiotic bacteria so that they are suitable for human consumption; 2) Making probiotic starter (Bacillus cereus SN7); 3) Pro coffee making; 4) Pro coffee packaging; and 5) Marketing of pro coffee products.